The City according to the Law of Fiscal Responsibility - Birck, Luiz Gilberto; Shikida, Pery Francisco Assis; Schallenberger, Erneldo (Review of Business Management, 2007)
Starting from May 5, 2000, with the publication of the Complementary Law # 101/2000, also called Law of Fiscal Responsibility (LRF), a new national guideline on administration of the patrimony, revenue, expense and public debts which the whole government is submitted to. This study analyzes this Law concerning the program planning and public actions, mainly in the ambit of the municipal district, supplying a technical vision on new fiscal responsibilities that are reaching all the public managers. Therefore, this study hopes to contribute to point out the complex relationships that are underlying the new juridical ordination, aiding the members of the society for the understanding of the new obligations and limits imposed for the public agents. Key-words: Fiscal responsibility. Public governments. Planning.